Neue Skulptur (Wien : Galerie nächst St. Stephan, 1982)
Adrian X, Robert ; Ahearn, John ; Anzinger, Siegfried ; Bömmels, Peter ; Buthe, Michael ; Butterfield, Deborah ; Chaimowicz, Marc Camille ; Cragg, Tony ; Dokoupil, Jiri Georg ; Eigenheer, Marianne ; Etter, Olivia ; etc.
Neue Skulptur, Galerie nächst St. Stephan, Wien, Juni - Juli 1982
Duits
kunstcatalogus